MUHAMMADIYAH DAN KONSEP DARUL AHDI WA SYAHADAH: REORIENTASI PEDAGOGI KEBANGSAAN DI ERA KONTEMPORER - Johan, Erni; Fardiansyah, Yuke; Mardiana, Dina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze and reconstruct the concept of Darul Ahdi wa Syahadah from a pedagogical perspective as a strategy to strengthen the integration of religious and national values in Muhammadiyah educational institutions. The study is motivated by the persistent dichotomy between religious identity and national commitment, as well as the increasing challenges of radicalism in education. This research employs a qualitative approach using a literature review method. Data were analyzed through content analysis and a critical hermeneutic approach.The findings indicate that Darul Ahdi wa Syahadah is not merely a theological concept but also has significant pedagogical implications in shaping inclusive, moderate, and progressive student character. The novelty of this study lies in the formulation of a value-based civic pedagogy model integrating theological, civic, and social praxis dimensions. This study recommends strengthening the role of educators as agents of value transformation within progressive Islamic education